Hypertension as a Determinant of Elevated Stress Among Hajj Pilgrims: A Cross-Sectional Study - Faridj Maulana Amir; Elman Boy; Ahmad Handayani; Nurhasanah (Universitas Muhammadiyah Malang, 2026)
Introduction: The Hajj pilgrimage involves physically and mentally demanding rituals under extreme conditions, including heat, crowding, and long travel, which can increase psychological stress. Hypertension may worsen this stress due to higher risk of complications and altered stress responses. This study aimed to evaluate hypertension as a determinant of stress among Hajj pilgrims in Medan in 2024. Methods: An analytic cross-sectional study was conducted on 56 pilgrims, divided into two groups: 28 with hypertension and 28 without. Stress levels were measured using the Perceived Stress Scale (PSS-10) and analyzed using the chi-square test. Results: There was a significant association between hypertension and stress levels (p < 0.05). Pilgrims with hypertension had higher stress levels compared to those without hypertension. Discussion: Hypertension is associated with increased stress among Hajj pilgrims. Concerns about health risks during demanding rituals may heighten psychological burden. Proper hypertension management and psychological support before and during Hajj are important to reduce stress and improve pilgrims’ well-being.